Shoulder Impingement Syndrome, A Common Shoulder Disease: A Comprehensive Review - Zhu, Junshuai (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The shoulder joint is a flexible but unstable joint in the human body. Also, it has complex structures including coracoacromial arch, synovial bursa, head of femur and so on. Based on these traits, shoulder joints have a wide range of activity, but some lesions accompany with, especially some overhand motions like throwing baseball, swimming, lifting the weight above head repetitively. Diversification of pathogenic factors are significant traits of this kind of injury. In addition, lesions of shoulder impingement syndrome (SIS) can occur in multiple locations even happening at same time. Under normal conditions, this type of disease is often delimited by rotator cuff. Because of the complexity of this injury, different tests of diagnosis can be applied, including Hawkins-Kennedy test, Neer sign, Jobe test, Painful arc of motion. For treatment options, these can be divided into conservative treatment including conservative methods and surgical treatment like arthroscopic subacromial decompression (ASD). SIS causes shoulder pain to disrupt and reduce life’s quality of patients. Based on relevant research and literature, this article is designed to offer a general review of the above content.